Behavioural competencies for asset manager’s roles on federal facilities asset management in Malaysia - Norazrin Mohd Kamarudzaman; Syahrul Nizam Kamaruzzaman (Penerbit Universiti Kebangsaan Malaysia, 2018)
The asset management in Malaysia is rapidly developing as it has shown to positively impact the industry. This development has emphasised the importance of an asset manager’s duties and responsibilities in order to achieve a productive and competent asset manager, specifically within the government sector. Therefore, it is important to investigate the ideal behavioural competencies needed in an asset manager. This study focuses on the identification of the roles and responsibilities of asset managers in managing the federal assets such as building and its facilities. This paper also investigates the ideal behavioural competencies needed in an asset manager and the relationship between the effect of their behaviour and their roles and responsibilities in managing the federal asset. In order to achieve the research objective, methods such as a literature review and a survey questionnaire were used. A literature review explores all of the variables and information and it was then used to form a questionnaire. Data collected from the questionnaires were analysed using descriptive statistics, correlation and factor analysis. Results of the study found that there are a total of seventeen (17) main roles and responsibilities and six (6) ideal behaviour of an asset manager. The results of this study also showed the relationship between the behaviour and the duties and responsibilities of asset managers as positive behaviour are needed in other in order to productively and effectively carry out their roles and responsibilities. To ensure effective comprehensive asset management in the federal facilities sector, it is suggested for all the federal ministries, department and agencies to increase and develop behavioural competencies that lie within their asset manager.